Analisis Sikap Intoleran Dikalangan Peserta Didik Di SMP Negeri 4 Lalan - Siti Nurinayah; Yuniar Yuniar; Ibnu Rozali (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to analyze intolerant attitudes among students at SMP Negeri 4 Lalan, as well as identify the causal factors and solutions to overcome them. The main problem found is the persistence of intolerant behavior such as judging each other, a lack of mutual assistance, and teasing among peers. This study used a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation with informants consisting of homeroom teachers, PPKn teachers, and student representatives. The results of the study indicate that intolerant attitudes arise due to internal factors, such as students' limited understanding of diversity, as well as external factors, such as the influence of the family environment, peers, and social media. These attitudes negatively impact the learning climate and character development of students. Solutions offered include instilling an attitude of tolerance from an early age and implementing cooperative learning in the classroom. Both approaches are considered effective in building empathy, mutual respect, and an inclusive school environment. Thus, education plays a crucial role in preventing the growth of intolerant attitudes and shaping a generation that values differences